RELATIONSHIP ANALYSIS OF WHOLE BODY VIBRATION (WBV) WITH MUSCULOSKELETAL DISORDER (MSDS) COMPLAINTS ON HEAVY EQUIPMENT OPERATORS AT THE TRANS SU-MATRA TOLL ROAD CONSTRUCTION PROJECT AT PT. ADHI KARYA TBK - Kesuma, Citra Retya; Malaka, Tan; Novrikasari, Rika (BIOVALENTIA: Biological Research Journal, 2019)
The use of heavy equipment in the construction field is very helpful in the process of a project. Heavy equipment operators exposed to the Whole Body Vibration due to a machine that can be transmitted through a seat or on the floor. These vibrations at certain intensities can lead to Musculoskeletal Disorder. This study aimed to analyze the relationship of Whole Body Vibration with the occurrence of Musculoskeletal Disorder complaints on Heavy Equipment Operators. Methods this study used cross sectional design, with a measuring instrument in the form of an accelerometer type 100A svantek and a Nordic Body Map questionnaire. The research sample was 45 operators with heavy equipment consisting of excavators, bulldozers, motorgrade, vibro compactors and dump trucks. WBV data retrieval is done when the operator works,, the tool is placed in the seat where the operator sits. Results of the study can be obtained through exposure to WBV based on ISO 2631: 1 15 heavy equipment operators (33.3%) were in the low WBV exposure category, while 30 operators (66.6%) in the Moderate and High category. Parts of the body which can be categorized as belonging to Work-related is part of Lower Back 99.35% (P Value 0.043; NK_R2 0.304) with BMI (OR 0.925) as the confounding variable. It can be concluded that the complaints Musculoskeletal Disorder (MSDs) in the Lower back may come from the presence of vibration exposure Whole Body Vibration generated from his job as a heavy equipment operator. Advised the company's management can reduce complaint rates by reducing operator exposure received.Keywords: Secondary metabolites, Trichoderma harzianum, Colletotrichum capsici, tannin